Cation reducibility of LaNi0.5Ti0.5O3, LaNi0.5Ti0.45Co0.05O3, and LaNi0.45Co0.05Ti0.5O3 perovskites from X-ray powder diffraction data using the Rietveld method. Issue 2 (June 2022) - Guamán-Ayala, Mayra; Tuza, Pablo V.; Souza, Mariana M. V. M.
Abstract : In the present work, LaNi0.5 Ti0.5 O3, LaNi0.5 Ti0.45 Co0.05 O3, and LaNi0.45 Co0.05 Ti0.5 O3 perovskites were synthesized using the modified Pechini method. After reduction, the studied perovskites changed crystal structure from the perovskite crystal structure to a cubic symmetry, with space group Pm3m . The reduction partially decomposed the samples to Ni 0 (Co free perovskite), Ni 0 –Co 0, La2 O3, La2 TiO5, and non-stoichiometric La2 NiO4, depending on H2 content of the reductive gases. The degree of reduction of nickel from LaNi0.5 Ti0.5 O3 reduced with 1.8% H2 /Ar and 10% H2 /Ar was equal to 36.5% and 95.3%, respectively, while that from LaNi0.5 Ti0.45 Co0.05 O3 or LaNi0.45 Co0.05 Ti0.5 O3, including cobalt, reduced with 10% H2 /Ar, was equal to 71.9% and 93.9%, respectively. LaNi0.5 Ti0.45 Co0.05 O3 showed Ni 3+ and Co 3+ amounts higher than the other perovskites. By increasing H2 content in the reductive mixture from 1.8% to 10%, sintering of metallic nickel was not observed. Moreover, Ni 0 displayed weaker metal–support interaction than that observed for Co 0, where the support was composed of La containing oxides. LaNi0.5 Ti0.5 O3 perovskite was used as a catalyst for steam reforming of methane. Syngas production was attributed to the number of Ni sites determined using Rietveld Refinement of X-ray diffraction pattern of this catalyst after the reaction.